Nutrient content in Quercus ilex canopies: seasonal and spatial variation within a catchment - Sabate, S; Sala, Anna; Gracia, C A (Plant and Soil, 1995)
Spatial and temporal changes in canopy nutrient content were studied in 1988 and 1989 in a Mediterranean Quercus ilex ssp. ilex L. forest in north-eastern Spain. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a small catchment (ridge top at 975 m and valley bottom at 700 m). Deeper soils resulted in significantly higher N and P concentrations, and N content on a leaf area basis at the valley bottom site. In contrast, K concentration in leaves was significantly higher at the ridge top site, where soil K concentration was also higher. At both sites, N and P content on a leaf area basis was highest at the top of the canopy, where leaf area is highest. N resorption efficiency decreased from top to bottom of the canopy. Results suggested a minor role of shaded leaves as nutrient storage sites. Lower P resorption efficiency was found at the ridge top site. Seasonal changes of P and N concentration on a leaf area basis suggest P replenishment, and to a lesser degree N, during periods of lower growth activity due to low temperatures, but coinciding with higher water availability (autumn-early spring period). Thus, N and P resorption from the remaining foliage in the canopy took place, and to a larger degree at the valley bottom site, coinciding with a slightly higher leaf area index and productivity at this site.
Keywords: Canopy; nutrient content and dynamics; nutrient resorption; Quercus ilex

Site-specific water relations and stomatal response of Quercus ilex in a Mediterranean watershed - Sala, Anna; Tenhunen, John D (Tree Physiology, 1994)
Intraspecific variations in the water relations and stomatal response of Quercus ilex L. were analyzed under field conditions by comparing trees at two locations within a Mediterranean watershed (l'Avic, Catalonia, NE Spain). Distinct environmental gradients exist between the two sites (referred to as ridge top at 975 m and valley bottom at 700 m) with greater soil depth for water storage, reduced radiation, reduced wind and higher water vapor pressure deficits at the valley bottom than at the ridge top. Osmotic adjustment and changes in tissue elasticiity did not significantly increase drought resistance in the trees studied. The leaf-to-air vapor pressure difference (Δw) threshold for inducing stomatal closure was higher at the ridge top (15.6 kPa MPa−1 ± 0.5 SE) than at the valley bottom (9.8 kPa MPa−1 ± 1.0 SE). However, increases in Δw beyond the threshold were followed by greater reductions in leaf conductance of trees at the ridge top than at the valley bottom. At both sites, maximum leaf conductance was related to predawn shoot water potential which, in turn, was related to watershed stream flow. The effects of water deficits during the dry summer of 1989 were more severe in trees at the valley bottom than at the ridge top. During periods of high evaporative demand, site-specific differences in the control of water loss led to more conservative water use by trees at the ridge top and, thus, to even greater drought avoidance (higher predawn water potentials) in late summer.
10.1093/treephys/14.6.601
Keywords: Mediterranean sclerophylls; oak forest; oak watershed; Osmotic potential; Stomatal conductance; water potential